Prevalence of Low Back Pain Among Office Workers During the COVID-19 Pandemic in Various Countries: A Systematic Review - Intan, Yosephine Roma; Wulandari, Ririn Arminsih; Yuniar, Popy (Kesmas, 2025)
The COVID-19 pandemic has led to the implementation of work from home policies in almost all parts of the world. This policy has increased the onset of musculoskeletal disorders in workers, such as low back pain (LBP). This study aimed to examine the prevalence of LBP among office workers during the COVID-19 pandemic after implementing WFH policies. This study was performed using data from various countries to determine the relationship between LBP and several risk factors, specifically age, sex, physical activity, ergonomic factors, as well as work environment factors such as temperature, humidity, lighting, noise, and work duration. A systematic review was conducted using sub-population studies published from 2020 to 2022. The data was obtained from six electronic databases: ProQuest, ScienceDirect, Embase, Scopus, Ebsco Medline, and Cambridge Core. The prevalence of LBP in office workers was associated with age, ergonomics, and environmental factors: air temperature, humidity, and lighting. There was no specific relationship between sex, physical activity, and working duration when working from home during the COVID-19 pandemic.